Pengaruh Pengetahuan Perpajakan, Kesadaran Wajib Pajak Dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan Di Kecamatan Bojongloa Kaler - Arto, Geovanca; Kasir, Kasir (Politeknik Negeri Ambon, 2024)
The research objective is to provide a deep understanding of the set of factors that hold influence on tax compliance, so that either the government or stakeholders can take strategic steps to increase tax revenue. The quantitative method of research applied descriptive and verification approaches. Primary data is obtained directly from the sample under study through the distribution of questionnaires which are then analyzed using statistical test tools. While secondary data is obtained through documents and literature relevant to this research. Sampling was carried out through the application of purposive sampling techniques with the Slovin formula. The population in the study was 13,779 land and building taxpayers whose objects were located in Bojongloa Kaler District. With this population and a margin of error of 10%, the number of samples obtained in this study was 100 respondents in Bojongloa Kaler District. Based on the research results, it is concluded that there is a strong positive influence between taxation knowledge (X1) and taxpayer awareness (X2) on taxpayer compliance (Y) with a significance level of 0.000 (p < 0.005) and t count 4.482 > t table 1.984 for X1, and 0.000 (p < 0.005) with t count 3.783 > t table 1.984 for X2. However, there is no strong influence between the quality of fiscal services (X3) on taxpayer compliance (Y) with a significance level of 0.547 (p> 0.005) and t count 0.605 < t table 1.984. So it can be concluded that taxation knowledge and taxpayer awareness hold a strong influence on taxpayer compliance, while the quality of tax authorities' services does not hold a strong influence on taxpayer compliance. Â